“Implementación de un sistema semiautomático en el brazo de la torreta de una desenllantadora para evitar deformaciones y rayones en los aros durante el montaje y desmontaje de los neumáticos”. - Pérez Calala, Jordi Israel (2020)
The purpose of this technological proposal is to implement a semi-automatic system in the turret arm of a unloader, since there was a deficit in the operation of the mechanical system, resulting in scratches and deformations in the rings during the assembly and disassembly service of the tires. The bibliographic, scientific and descriptive methodology was used to determine the state of the art and by means of calculation, simulation and programming, the semi-automatic system was designed that allows the correct choice of the elements used in the system. The results obtained after the research process are satisfactory, because the mechanical system was replaced by a semi-automatic system in the turret arm that serves the same purpose but with different systems controlled by pneumatic and electrical controls. Therefore, it is concluded that the implementation carried out managed to control the involuntary movements of the turret bar, helping to eliminate deformations and scratches in the tire rings.